Employment protection and unemployment benefits : on technology adoption and job creation in a matching model - Lommerud, Kjell Erik (2012)
We analyse the effects of different labour market policies - employment protection, unemployment benefits and payroll taxes - on job creation and technology choices in a model where firms are randomly matched with workers of different productivity and wages are determined by ex-post bargaining. In this setting, unemployment benefits are unambiguously detrimental both to job creation and technology adoption while the effects of employment protection are mixed, as higher firing costs stifle job creation but stimulate technology investments. This suggests that a 'flexicurity' policy, with low employment protection and high unemployment benefits, might have the adverse effect of slowing down technological progress and job growth. Indeed, our analysis of the optimal policy solution suggests that flexicurity is often not optimal, and may be optimal only in conjunction with payroll subsidies.